2014
DOI: 10.1002/jrs.4532
|View full text |Cite
|
Sign up to set email alerts
|

Raman investigation of artificial patinas on recent bronze protected by different azole type inhibitors in an outdoor environment

Abstract: Bronze surfaces, as well as prepatinated surfaces on bronze, undergo chemical and visual changes when exposed to humid and polluted environments. For this reason, it is important to study the effectiveness of corrosion inhibitors on patinated‐bronze surfaces. The aim of this study was to investigate different protection systems for patinated bronze, which are based on the use of two azole type inhibitors: 2‐mercaptobenzimidazole and benzotriazole. The results of our practice confirmed that these inhibitors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kosec and co‐workers reported on a Raman investigation of artificial patinas on recent bronze protected by different azole type inhibitors in an outdoor environment. The results of these Raman studies showed a chemical interaction of both inhibitors with copper and bronze but a versatile interaction between the inhibitors and the different patinas . Li and colleagues carried out both synthesis and a Raman study on needlelike silicates in ancient Chinese Pb–Ba glass from the Qin and Han dynasties.…”
Section: Art and Archeologymentioning
confidence: 99%
“…Kosec and co‐workers reported on a Raman investigation of artificial patinas on recent bronze protected by different azole type inhibitors in an outdoor environment. The results of these Raman studies showed a chemical interaction of both inhibitors with copper and bronze but a versatile interaction between the inhibitors and the different patinas . Li and colleagues carried out both synthesis and a Raman study on needlelike silicates in ancient Chinese Pb–Ba glass from the Qin and Han dynasties.…”
Section: Art and Archeologymentioning
confidence: 99%
“…To decrease those decaying processes, corrosion inhibitors started to be used some years ago, although the basic knowledge on their protective effect is not well clarified. To better understand the effectiveness of corrosion inhibitors on patinated bronze surfaces, Kosec et al . studied the adequacy of two azole type inhibitors.…”
Section: Conservation Issues (Alteration/degradation Processes) Affecmentioning
confidence: 99%